Effect of Recorded Maternal Voice on Emergence Delirium in Children Under General Anesthesia: A Randomized Controlled Trial. Issue 11 (20th November 2021) - Wang, Cong; Wang, Wei; Wang, Shuo; He, Rendong; Yang, Haiqi; Jia, Yong; Chen, Li
Abstract: To determine the effect of recorded maternal voice on emergence delirium (ED) in children under general anesthesia, a three-group randomized trial was conducted. A total of 102 children were randomly assigned to mother recording group ( n = 34), stranger recording group ( n = 34), and control group ( n = 34). All subjects were assessed for ED with the Pediatric Anesthesia Emergence Delirium Scale; pain with the Face, Legs, Activity, Cry, and Consolability Scale; and various recovery durations and hemodynamic parameters at six time points. One-way analysis of variance showed that the ED score was significantly lower in the mother recording group ( F = 18.520, p = 0.000), and statistical significance was observed in the duration of eye opening ( p = 0.001) and tracheal extubation ( p = 0.002). Generalized estimating equations observed interaction effects on heart rate and blood pressure (both p = 0.000). Mothers' voice might help reduce ED in children under general anesthesia.